Recommendations for the management of hip and knee osteoarthritis: A systematic review of clinical practice guidelines - Gibbs, Alison J.; Gray, Bimbi; Wallis, Jason A.; Taylor, Nicholas F.; Kemp, Joanne L.; Hunter, David J.; Barton, Christian J. (Osteoarthritis and cartilage, 2023)
Guideline adherence for hip and knee osteoarthritis management is often poor, possibly related to the quality and/or inconsistent recommendations. This systematic review of hip and knee osteoarthritis guidelines aimed to appraise the quality and consistency in recommendations across higher-quality guidelines. Eight databases, guideline repositories, and professional associations websites were searched on 27/10/2022. Guideline quality was appraised using the Appraisal of Guidelines for Research and Evaluation II (AGREE II tool) (six domains). Higher quality was defined as scoring ≥60% for domains 3 (rigour of development), 6 (editorial independence), plus one other. Consistency in recommendations across higher-quality guidelines was reported descriptively. This review was registered prospectively (CRD42021216154). Seven higher-quality and 18 lesser-quality guidelines were included. AGREE II domain scores for higher-quality guidelines were > 60% except for applicability (average 46%). Higher-quality guidelines consistently recommended in favour of education, exercise, and weight management and non-steroidal anti-inflammatory drugs (hip and knee), and intra-articular corticosteroid injections (knee). Higher quality guidelines consistently recommended against hyaluronic acid (hip) and stem cell (hip and knee) injections. Other pharmacological recommendations in higher-quality guidelines (e.g., paracetamol, intra-articular corticosteroid (hip), hyaluronic acid (knee)) and adjunctive treatments (e.g., acupuncture) were less consistent. Arthroscopy was consistently recommended against in higher-quality guidelines. No higher-quality guidelines considered arthroplasty. Higher-quality guidelines for hip and knee osteoarthritis consistently recommend clinicians implement exercise, education, and weight management, alongside consideration of Non-Steroidal Anti-Inflammatory Drugs and intra-articular corticosteroid injections (knee). Lack of consensus on some pharmacological options and adjunctive treatments creates challenges for guideline adherence. Future guidelines must prioritise providing implementation guidance, considering consistently low applicability scores.